INSIDENSI PENYAKIT BUSUK BUAH PALA DI KECAMATAN KENDAHE KABUPATEN KEPULAUAN SANGIHE - Virnansia A. Karoho; Denny Sualang; Max Ratulangi (COCOS, 2016)
ABSTRACKThis study aimed to quantify the incidences of dry-rot and wet-rot fruit diseases in some centers of nutmeg plantations, namely the Village of Talawid, Kendahe Satu, and Kendahe Dua, Kendahe Sub-District, The District of Sangihe Islands. This study was done for 4 months from October 2015 to January 2016. This study used a survey method with a purposive sampling in nutmeg plantations owned by the farmers in the village of Talawid, Kendahe Satu, and Kendahe Dua, each village was assigned one farm as a sample. The nutmeg tree was divided into two sectors, namely the upper and lower sector. The number of sample nutmeg trees were 20 trees; each sector of the tree was randomly observed 30 nutmeg. Observations were made three times at intervals of two weeks, of different nutmeg trees.The results of this study showed that early symptoms of dry-rot fruit disease appeared small brown rounded patches, with a diameter of approximately 0.3 cm, this section become brown and sunken (concave), while the wet-rot fruit disease, symptoms generally begin to appear at the base of the fruit, in which the diseased part started to become brown. The causal agent of dry-rot fruit disease is Stigmina myristicae, while wet-rot fruit disease caused by Colletotrichum gloeosporioides. The incidences of fruit rot disease in the observed center nutmeg plantations showed diffrent disease incidences. The highest average incidences of wet-rot fruit disease was 3.92%, while the highest average incidences of dry-rot fruit disease was 56.18%.Key Words: Nutmeg, Stigmina myristicae, Colletrotrichum gloeosporiodes, Incidences